Low-refractive-index polyester composition as well as preparation method and application thereof
By copolymerizing aromatic and cycloaliphatic dibasic acids, specific diols and adding titanium-based catalysts and phosphorus compounds, the composition of the low-refractive index polyester composition is optimized, and the problems of poor heat resistance and high-gel substances during fusion heat processing in the prior art are solved, thereby realizing the preparation of high-quality films.
Patent Information
- Application Number
- CN202311388312.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing low-refractive index polyester compositions have poor heat resistance during melting and heat processing, which easily produces foreign matter and gel substances, affecting the quality and yield of the film.
By copolymerizing aromatic dicarboxylic acids, alicyclic dicarboxylic acids, specific diols and adding titanium-based catalysts and phosphorus compounds, the composition and structure of the polyester composition is optimized, the refractive index is reduced and the formation of gels is reduced.
High heat resistance and low gel rate of low refractive index polyester composition during melt heat processing are achieved, and the quality and yield of the film are improved.
Smart Images

Figure BDA0004514777510000011 
Figure BDA0004514777510000021 
Figure BDA0004514777510000022
Abstract
Description
Technical Field
[0001] The present invention relates to a low-refractive-index polyester composition, a preparation method and use thereof, and specifically to a polyester resin obtained by copolymerizing an alicyclic dibasic acid or an esterified derivative thereof and an alicyclic and / or side-chain aliphatic diol, which has a low refractive index, few foreign matters and generates little gel during melt heat processing, and a preparation method thereof. Background Art
[0002] Laminated films prepared by alternating polymers with different refractive indices are often used as optical filters and light reflectors because they can effectively reflect light of a specific wavelength. Such laminated films are composed of two or more polymers, and the polymer used in the low refractive index layer is generally a copolymerized polyester composition in consideration of the adjustment of the refractive index and the adhesion between the layers. However, the low refractive index polyester composition currently used has poor heat resistance due to the influence of the copolymerized components, and is prone to foreign matter during melt extrusion in the film manufacturing process, resulting in many film defects, which greatly reduces the film yield.
[0003] In order to improve the heat resistance of a polyester composition, Japanese Patent Laid-Open No. 2003-020330 discloses a polyester resin, which is composed of dicarboxylic acid units mainly composed of terephthalic acid units and 1,4-cyclohexanedicarboxylic acid units and / or isophthalic acid units, and diol units mainly composed of ethylene glycol units and 1,4-cyclohexanedimethanol units. The polyester has excellent molding processability and impact resistance. However, the 1,4-cyclohexanedicarboxylic acid units and ethylene glycol units are easily thermally decomposed to produce foreign matter, resulting in poor heat resistance of the polyester composition. This patent does not provide a solution to this technical problem. Summary of the invention
[0004] The object of the present invention is to provide a polyester composition having a low refractive index and generating little gel during melt heat processing and a method for preparing the same. The low refractive index polyester composition is mainly used for preparing a laminated film.
[0005] The technical solution of the present invention:
[0006] A low-refractive index polyester composition mainly comprises an aromatic dicarboxylic acid unit, an alicyclic dicarboxylic acid unit, a diol unit as shown in Formula 1, and a diol unit as shown in Formula 2 and / or Formula 3;
[0007]
[0008] In formula 1, R 1 It is a chain alkylene group having 2 to 10 carbon atoms;
[0009]
[0010]
[0011] In formula 2 and formula 3, R 2 is a cyclic alkylene group having 3 to 10 carbon atoms, R 3 ~R 6 are alkylene groups having 0 to 10 carbon atoms, R 7 ~R 8 Each of them is an alkyl group having 1 to 10 carbon atoms.
[0012] The low refractive index polyester composition contains titanium and phosphorus. The content of the titanium is equivalent to 1-100 ppm of the total amount of the polyester composition. The molar ratio of the titanium to the phosphorus is 0.05-2.00.
[0013] The alicyclic dibasic acid unit preferably accounts for 10 to 50 mol% of the total dibasic acid unit content.
[0014] The sum of the diol units shown in Formula 2 and Formula 3 preferably accounts for 5 to 90 mol% of the total diol unit content.
[0015] The refractive index of the low refractive index polyester composition is preferably 1.500-1.570, and the glass transition temperature is preferably 50-100° C. The gel fraction of the polyester composition after heat treatment at 280° C.×24 hr in a nitrogen atmosphere is preferably less than 10.0 wt %. The Haze content of the polyester composition is less than 5%.
[0016] The present invention also discloses a method for preparing the low-refractive index polyester composition, wherein dicarboxylic acid or its esterified derivative and diol are used as main monomers, and an esterification kettle is added to perform esterification or ester exchange reaction to obtain a small molecule polymer, and then the small molecule polymer is subjected to polycondensation reaction to obtain the low-refractive index polyester composition. The dicarboxylic acid or its esterified derivative includes aromatic dicarboxylic acid or its esterified derivative and alicyclic dicarboxylic acid or its esterified derivative; the diol includes diol as shown in Formula 4, and diol as shown in Formula 5 and / or Formula 6;
[0017] HO-R 1 -OH Formula 4,
[0018] In formula 4, R 1 It is a chain alkylene group having 2 to 10 carbon atoms;
[0019] HO-R 3 -R 2 -R 4 -OH Formula 5,
[0020]
[0021] In equations 5 and 6, R 2is a cyclic alkylene group having 3 to 10 carbon atoms, R 3 ~R 6 are alkylene groups having 0 to 10 carbon atoms, R 7 ~R 8 Each of them is an alkyl group having 1 to 10 carbon atoms.
[0022] A titanium catalyst and a phosphorus compound are added during the polymerization process, wherein the amount of the titanium catalyst added is 1 to 100 ppm relative to the total amount of the polyester composition in terms of titanium element, and the amount of the titanium catalyst and the phosphorus compound added is 0.05 to 2.00 in terms of the molar ratio of the titanium element to the phosphorus element.
[0023] The titanium-based catalyst is preferably tetraethoxytitanium, tetrapropoxytitanium, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetrahexyloxytitanium, tetra-2-ethylhexyloxytitanium, tetraoctyloxytitanium, monohydroxytriethoxytitanium, monohydroxytripropoxytitanium, monohydroxytriisopropoxytitanium, monohydroxytributoxytitanium, dihydroxybisethoxytitanium or trihydroxyisopropoxide titanium.
[0024] The phosphorus compound is preferably phosphoric acid, sodium dihydrogen phosphate, triethyl phosphoacetate, trimethyl phosphoacetate or triphenyl phosphate.
[0025] The invention sets the amounts of the titanium catalyst and the phosphorus compound within a certain ratio range, so that the low-refractive index copolymerized polyester composition generates less gel during melt heat processing, and is suitable for the film field. DETAILED DESCRIPTION
[0026] The polyester resin formed by a simple aromatic dibasic acid or its esterified derivative and an aliphatic straight-chain diol has high crystallinity. When the film formed by the polyester resin is stretched under stress, it will be oriented, which will cause the optical properties of the film to change. By replacing part of the aromatic dibasic acid units with alicyclic dibasic acid units, the crystallinity and refractive index of the polyester can be reduced, and a low-refractive-index polyester composition can be obtained.
[0027] If the content of the alicyclic dicarboxylic acid unit is too low, the number of substituted aromatic dicarboxylic acid units is too small, and the refractive index of the polyester composition is not significantly reduced. If the content of the alicyclic dicarboxylic acid unit is too high, the polymerization reaction activity is poor, the time required to reach the target melt viscosity is long, and the color tone and heat resistance of the obtained polyester composition are deteriorated; and because the alicyclic dicarboxylic acid unit is easily decomposed by heat under the action of the straight-chain aliphatic diol, and the ester bond formed by the alicyclic dicarboxylic acid unit and the straight-chain aliphatic diol unit as shown in Formula 1 is easily broken, the free radicals generated by these decompositions and breaks are prone to chain reactions, such as the generation of carbides, or the formation of bridge structures by bridging reactions between molecules, all of which will cause defects in the polyester composition during the film-making process. Therefore, based on the comprehensive consideration of the refractive index, gel fraction, reaction activity, etc. of the polyester composition, the content of the alicyclic dicarboxylic acid unit in the total dicarboxylic acid unit is preferably 10 to 50 mol%.
[0028] In view of the optical properties of the polyester composition, the alicyclic dicarboxylic acid unit of the present invention is preferably a 1,4-cyclohexanedicarboxylic acid unit or a 1,3-cyclohexanedicarboxylic acid unit. In addition, the cyclohexanedicarboxylic acid unit is usually a mixture of a cis-cyclohexanedicarboxylic acid unit and a trans-cyclohexanedicarboxylic acid unit. Since the trans-cyclohexanedicarboxylic acid unit easily affects the crystallinity of the polyester composition, the ratio of the trans-cyclohexanedicarboxylic acid unit is preferably less than 40%.
[0029] The aromatic dicarboxylic acid unit of the present invention can be selected from one or more of terephthalic acid unit, 2,6-naphthalene dicarboxylic acid unit, isophthalic acid unit, 5-sodium sulfoisophthalic acid unit, etc., among which terephthalic acid unit or 2,6-naphthalene dicarboxylic acid unit is preferred.
[0030] Although the introduction of alicyclic dicarboxylic acid units can reduce the refractive index of the polyester composition, it will also cause a decrease in the glass transition temperature (Tg) of the polyester composition. If the Tg of the obtained polyester composition is significantly different from that of conventional polyesters, it is difficult to form when used to prepare a laminated film, and the flatness of the formed film is poor, and it is easy to wrinkle or break.
[0031] The polyester composition of the present invention contains alicyclic diol units as shown in Formula 2 and / or aliphatic diol units with branches as shown in Formula 3 through copolymerization. The diol units as shown in Formula 2 and Formula 3 have large steric hindrance and can improve the rigidity of the polyester chain segment, thereby improving the Tg of the polyester composition and making it equivalent to the Tg of conventional polyester.
[0032]
[0033]
[0034] In formula 2 and formula 3, R 2 is a cyclic alkylene group having 3 to 10 carbon atoms, R 3 ~R 6 are alkylene groups having 0 to 10 carbon atoms, R 7 ~R 8 Each of them is an alkyl group having 1 to 10 carbon atoms.
[0035] At the same time, as shown in Formula 2 and Formula 3, the diol unit has a large steric hindrance and can effectively block the contact between the straight-chain aliphatic diol and the alicyclic dibasic acid unit, thereby reducing the thermal decomposition of the alicyclic dibasic acid unit, reducing the generation of foreign matter, and inhibiting the formation of gel.
[0036] The diol unit as shown in Formula 2 of the present invention is preferably 1,4-cyclohexanedimethanol unit or 1,4-dihydroxycyclohexane unit. The diol unit as shown in Formula 3 can be selected from one or more of neopentyl glycol (NPG) unit, 3,3-dimethyl-pentanediol unit, 4,4-dimethyl-heptanediol unit, etc., wherein the neopentyl glycol unit or 3,3-dimethyl-pentanediol unit is preferred.
[0037] In addition, the total amount of the diol units as shown in Formula 2 and Formula 3 in the polyester composition preferably accounts for 5 to 90 mol% of the total diol units. If the total content of the diol units as shown in Formula 2 and Formula 3 is too low, the Tg of the polyester composition cannot be effectively improved, and the thermal decomposition of the alicyclic dibasic acid units cannot be effectively inhibited, and the polyester composition generates more gel during melt heat treatment; if the total content of the diol units as shown in Formula 2 and Formula 3 is too high, the polymerization reaction activity is poor, the time required to reach the target melt viscosity is long, and the color tone and heat resistance of the obtained polyester composition are deteriorated.
[0038] The linear aliphatic diol unit represented by Formula 1 of the present invention can be selected from one or more of ethylene glycol unit, 1,3-propylene glycol unit, 1,4-butylene glycol unit, 1,5-pentanediol unit, 1,6-hexanediol unit, etc., among which ethylene glycol unit or 1,3-propylene glycol unit is preferred.
[0039] Due to the polymerization activity of comonomers such as alicyclic dibasic acids, alicyclic diols, and aliphatic diols with branches, a higher catalytic activity is required to achieve the usual polyester reaction rate. Generally, this can be achieved by increasing the content of conventional catalysts or using catalysts with high catalytic activity. Increasing the content of conventional catalysts will cause the catalyst to form foreign matter in the polyester composition, so the present invention selects a titanium catalyst with higher catalytic activity.
[0040] By adding a titanium catalyst during the polymerization process, the polyester composition contains 1 to 100 ppm of titanium element in the total amount of the polyester composition. If the content of the titanium element is higher than 100 ppm, the polymerization reaction catalytic activity and the side reaction catalytic activity are both high, which will promote the thermal decomposition of the alicyclic dicarboxylic acid unit and the cleavage of the ester bond formed by the alicyclic dicarboxylic acid unit and the straight-chain aliphatic diol unit as shown in Formula 1, produce foreign matter, and cause the generated polyester composition to easily generate gel after heating, and the decomposition of the diol unit with large steric hindrance as shown in Formulas 2 and 3 will cause the Tg of the polyester composition to be excessively increased, and it is not easy to form during lamination film formation, and the flatness of the film is not good, and it is easy to wrinkle or break; if the content of the titanium element is lower than 1 ppm, the polymerization reaction activity is poor, the time required to reach the target melt viscosity is long, and the color tone and heat resistance of the obtained polyester composition are deteriorated. In order to effectively inhibit the generation of foreign matter and maintain the conventional physical properties of the polyester composition, the present invention preferably contains 5 to 80 ppm of titanium element in the polyester composition.
[0041] The present invention also reduces the side reaction activity of the titanium catalyst by adding phosphide, thereby further inhibiting the generation of foreign matter in the polyester composition. The phosphorus compound achieves the effect of inhibiting the side reaction activity of the titanium catalyst by coordinating with the titanium catalyst. To achieve the effect of effectively inhibiting the side reaction activity of the titanium catalyst, the ratio of the titanium catalyst to the phosphorus compound must meet a certain range, which is reflected in the polyester composition as the molar ratio of titanium element to phosphorus element. When the molar ratio of the titanium element to the phosphorus element is less than 0.05, the phosphorus compound inhibits the catalytic activity of the titanium catalyst too much, the polymerization activity is poor, the time required to reach the target melt viscosity is long, and the color tone and heat resistance of the obtained polyester composition deteriorate; when the molar ratio of the titanium element to the phosphorus element is greater than 2.00, the phosphorus compound does not have a good catalytic activity inhibition effect. The present invention is more preferably that the molar ratio of the titanium element to the phosphorus element in the polyester composition is 0.10 to 1.00. Within this range, the polyester composition can have good heat resistance, less foreign matter, low gel rate, and appropriate Tg.
[0042] By selecting appropriate copolymer monomers and copolymer content, the refractive index of the polyester composition of the present invention can reach 1.500-1.570. In a further preferred technical solution, the refractive index can be 1.510-1.560, which is suitable for the preparation of laminated films.
[0043] In order to minimize the difference in glass transition temperature between polymers when preparing laminated films, avoid wrinkling of laminated films, and improve film stability, the glass transition temperature (Tg) of the polyester composition described in the present invention is preferably 50-100°C, more preferably 70-85°C.
[0044] The invention selects and limits copolymer components, and the gel fraction of the polyester composition after heat treatment at 280° C.×24 hr in a nitrogen atmosphere is less than 10.0 wt %.
[0045] Meanwhile, the polyester composition of the present invention has a small foreign matter content, and the foreign matter generated after heating is also low, and the Haze is below 5%.
[0046] The present invention also discloses a method for preparing the above-mentioned low-refractive index polyester composition, wherein dicarboxylic acid or its esterified derivative and diol are used as main monomers, and an esterification kettle is added to perform esterification or ester exchange reaction to obtain a small molecule polymer, and then the small molecule polymer is subjected to polycondensation reaction to obtain a polyester composition. The dicarboxylic acid or its esterified derivative is mainly an aromatic dicarboxylic acid or its esterified derivative and an alicyclic dicarboxylic acid or its esterified derivative; the diol is mainly a diol as shown in Formula 4, and Formula 5 and / or Formula 6;
[0047] HO-R 1 -OH Formula 4,
[0048] In formula 4, R 1 It is a chain alkylene group having 2 to 10 carbon atoms;
[0049] HO-R 3 -R 2 -R 4 -OH Formula 5,
[0050]
[0051] In equations 5 and 6, R 2 is a cyclic alkylene group having 3 to 10 carbon atoms; R 3 ~R 6 are alkylene groups having 0 to 10 carbon atoms; R 7 ~R 8 Each of them is an alkyl group having 1 to 10 carbon atoms.
[0052] A titanium catalyst and a phosphorus compound are added during the polymerization process, and the amount of the titanium catalyst added is 1 to 100 ppm relative to the total amount of the polyester composition in terms of titanium element. If the amount of the titanium catalyst added is higher than 100 ppm in terms of titanium element, the catalytic activity of the polymerization reaction and the catalytic activity of the side reaction are both high, which will promote the thermal decomposition of the alicyclic dicarboxylic acid and the cleavage of the ester bond formed by the alicyclic dicarboxylic acid and the straight-chain aliphatic diol as shown in Formula 4, produce foreign matter, and cause the generated polyester composition to easily form gel after heating, and the film produced is prone to produce defects. If the amount of the titanium catalyst added is lower than 1 ppm in terms of titanium element, the polymerization reaction activity is poor, the time required to reach the target melt viscosity is longer, and the color tone and heat resistance of the obtained polyester composition deteriorate. In order to effectively suppress the generation of foreign matter while maintaining the conventional physical properties of the polyester composition, the present invention preferably adds 5 to 80 ppm of the titanium catalyst in terms of titanium element.
[0053] The titanium catalyst can be a titanium-containing catalyst commonly used in polymerization reactions, preferably tetraethoxytitanium, tetrapropoxytitanium, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetrahexyloxytitanium, tetra-2-ethylhexyloxytitanium, tetraoctyloxytitanium, monohydroxytriethoxytitanium, monohydroxytripropoxytitanium, monohydroxytriisopropoxytitanium, monohydroxytributoxytitanium, dihydroxybisethoxytitanium or trihydroxyisopropoxytitanium. The aforementioned titanium catalysts can be used alone or in combination. Among them, tetraethoxytitanium, tetrapropoxytitanium, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetrahexyloxytitanium, and tetraoctyloxytitanium are low in cost and easy to react, so they are more preferred.
[0054] In order to coordinate with the titanium catalyst and appropriately inhibit the catalytic activity of the titanium catalyst, the phosphorus compound is added in an amount that satisfies the molar ratio of titanium element to phosphorus element of 0.05 to 2.00. In the preferred range of 0.10 to 1.00, the polyester composition can have good heat resistance, less foreign matter, low gel fraction and appropriate Tg.
[0055] The phosphorus compound is preferably phosphoric acid, sodium dihydrogen phosphate, triethyl phosphoacetate (TEPA), trimethyl phosphoacetate (TMPA) or triphenyl phosphate. The aforementioned phosphorus compounds can be used alone or in combination.
[0056] In order to prevent unnecessary degradation and / or branching reactions, an appropriate amount of alkaline compounds, such as sodium hydroxide, potassium hydroxide, tetraethylammonium hydroxide, disodium hydrogen phosphate, etc., may be added during the reaction.
[0057] The low refractive index polyester composition described in the present invention has good color tone and transparency, excellent heat resistance, less foreign matter, less gel generated during melt heat processing, and the laminated film prepared by alternating with conventional polyesters has excellent light reflectivity and heat reflectivity, and is suitable for optical filters and light reflectors.
[0058] The determination methods and evaluation methods of various indicators of the present invention are as follows:
[0059] (1) Carboxyl content (COOH)
[0060] The optical titration method was used to determine the polyester chips. The polyester chips were dissolved in a mixture of o-cresol and chloroform (weight ratio 70:30), bromothymol blue indicator was added, and then titrated with 0.05 mol / L potassium hydroxide ethanol solution (the average value was taken after two tests).
[0061] (2) Glass transition temperature (Tg)
[0062] Weigh 10 mg of the sample and put it into a crucible for sample preparation, and use a differential scanning calorimeter (DSC, manufacturer: model:) for measurement. Measurement conditions: the test temperature is raised from 20°C to 280°C in a nitrogen atmosphere, with a heating rate of 16°C / min, then quenched with liquid nitrogen, and then the test temperature is raised from 20°C to 280°C in a nitrogen atmosphere again, with a heating rate of 16°C / min, and finally the temperature is lowered from 280°C to 20°C, with a cooling rate of 16°C / min. A total of three curves are obtained, and the glass transition temperature of the second curve is obtained.
[0063] (3) Refractive index
[0064] The polyester composition was melt-extruded to obtain an unstretched film having a thickness of 100 μm, and the D-light refractive index was measured using an ATAGO Abbe refractometer (model NAR-4T) at 23° C. using a sodium lamp as the illumination source.
[0065] (4) Gel rate
[0066] The polyester composition is crushed into a powder with a particle size of less than 300 μm, and 0.5000-0.5999 g of the powder is taken as a sample, and dried at 50°C under vacuum conditions for more than 2 hours. The dried sample is passed through a nitrogen-oxygen mixed gas with an oxygen concentration of 1 vol% and heat-treated at 300°C. After 6 hours, it is taken out and cooled to room temperature. The heat-treated sample is dissolved in 20 ml of hexafluoroisopropanol (HFIP) at room temperature for 1 hour, then filtered with a 400-800 mesh metal filter, and then washed with dichloromethane. Finally, the HFIP insoluble matter is dried and weighed. The calculation formula for the gel fraction is as follows (the average value is taken after two tests):
[0067] Gel ratio (wt%) = (weight of HFIP insoluble matter / weight of sample) x 100%.
[0068] (5) Polyester composition HAZE
[0069] 2.0 g of the polyester composition chips were dissolved in 20 ml of o-chlorophenol solution and tested using HZ-V3 HAZE tester manufactured by Suga Test Instruments. Each sample was tested three times and the average value of the three tests was calculated.
[0070] (6) Determination of element content in polymer
[0071] A certain amount of polyester composition is taken and spectrally analyzed using fluorescent X-rays to qualitatively identify elements such as phosphorus, manganese, magnesium, and titanium, and to quantitatively determine the element content based on the intensity of the spectrum (the average value is taken after two tests).
[0072] (7) Determination of the content of each component unit in the polyester composition
[0073] Take a certain amount of the polyester composition, use H-NMR to test the hydrogen spectrum of the polyester composition, and find the area of the characteristic peak of the hydrogen element of each component (for example, the characteristic peak of the hydrogen element on the aromatic ring, the characteristic peak of the hydrogen element on the straight-chain fatty structure, the characteristic peak of the hydrogen element on the alicyclic structure, the characteristic peak of the hydrogen element on the heterocyclic structure, etc.), and calculate the content of each component unit in the polyester composition.
[0074] (8) Hue b value
[0075] Determined according to national standard GB / T 14190-1993 (average value after three tests).
[0076] (9) Heat resistance %BB
[0077] 8 g of polyester composition chips were placed in two small test tubes respectively, and heated at 300°C for 1 hour under nitrogen. The terminal COOH before the heat treatment and the terminal COOH after the 1-hour treatment were compared. The ratio of ester bonds broken by thermal decomposition was calculated based on the change in the terminal COOH.
[0078] %BB = 50 × 192 × (terminal COOH after heat treatment / 1000000-terminal before heat treatment / 1000000)
[0079] The advantages of the present invention will be described in detail below by referring to the following examples and comparative examples. The present invention is not limited to the following examples.
[0080] Example 1
[0081] 48.5 parts by weight of dimethyl terephthalate (DMT), 16.7 parts by weight of dimethyl 1,4-cyclohexanedicarboxylate (CHDC), 35.1 parts by weight of ethylene glycol (EG), 14.4 parts by weight of 1,4-cyclohexanedimethanol (CHDM), 0.06 parts by weight of manganese acetate (MNA), and 0.005 parts by weight of potassium hydroxide (KOH) were added to an esterification reaction kettle, and the mixture was dissolved at 150° C. while stirring, and then an ester exchange reaction was started. The temperature in the esterification kettle reached 220° C. under the set heating program, and the by-product methanol was distilled out. When the distilled methanol reached a specified amount, the temperature in the esterification kettle was continued to be raised. After 30 minutes, the temperature in the kettle reached 230° C., and the excess EG in the esterification kettle was distilled out to obtain a small molecule polymer.
[0082] The obtained small molecule polymer is transferred to a polymerization kettle with a waiting temperature of 225°C. Five minutes after the transfer, triethyl phosphoacetate (TEPA) equivalent to 60 ppm of the total amount of polyester in terms of phosphorus is added. After stirring for 15 minutes, tetrabutyl titanate (TBT) equivalent to 20 ppm of the total amount of polyester in terms of titanium is added. Next, the polycondensation reaction is started by reducing pressure and increasing temperature. The temperature is increased from 225°C to 285°C and the pressure is reduced to 25Pa. The final temperature and final pressure are reached in 90 minutes. After a period of time, the melt viscosity of the reaction polymer system reaches 2000poise and is discharged. The polymerization time from the beginning of reducing pressure and increasing temperature to the final discharge is 2 hours and 50 minutes. When discharged, the polymer is in a uniform strip shape. After cooling in a water tank, it is pelletized to obtain polyester composition slices.
[0083] The specific formula and physical properties are shown in Table 1.
[0084] Embodiments 2 to 22
[0085] The preparation process is the same as in Example 1, and the specific formula and physical properties are shown in Tables 1 and 2.
[0086] Comparative Example 1
[0087] 66.3 parts by weight of CHDC, 35.1 parts by weight of EG, 14.4 parts by weight of CHDM, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring, and then the ester exchange reaction was started. The temperature in the esterification reactor reached 220°C under the set temperature increase program, and the by-product methanol was distilled out. When the distilled methanol reached the specified amount, the temperature in the esterification reactor was continued to be increased. After 30 minutes, the temperature in the reactor reached 230°C, and the excess EG in the esterification reactor was distilled out to obtain a small molecule polymer.
[0088] The obtained small molecule polymer was transferred to a polymerization kettle at a waiting temperature of 225°C. 5 minutes after the transfer, TEPA equivalent to 60ppm of the total amount of polyester in terms of phosphorus was added. After stirring for 15 minutes, TBT equivalent to 20ppm of the total amount of polyester in terms of titanium was added. Then, the polycondensation reaction was started by reducing the pressure and increasing the temperature from 225°C to 285°C and reducing the pressure to 25Pa. The final temperature and final pressure were reached in 90 minutes. After a period of reaction, the polymerization reaction was not completed, the reaction was terminated, and no polyester composition was obtained. The specific formula and physical properties are shown in Table 4.
[0089] Since the dicarboxylic acid in the polymerization raw material only contains alicyclic dicarboxylic acid and no aromatic dicarboxylic acid with good rigid structure, the polymerization reaction activity is poor and the target polyester composition cannot be obtained.
[0090] Comparative Example 2
[0091] 64.7 parts by weight of DMT, 35.1 parts by weight of EG, 14.4 parts by weight of CHDM, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring, and then the ester exchange reaction was started. The temperature in the esterification reactor reached 220°C under the set heating program, and the by-product methanol was distilled out. When the distilled methanol reached the specified amount, the temperature in the esterification reactor was continued to be raised. After 30 minutes, the temperature in the reactor reached 230°C, and the excess EG in the esterification reactor was distilled out to obtain a small molecule polymer.
[0092] The obtained small molecule polymer was transferred to a polymerization kettle at a waiting temperature of 225°C. Five minutes after the transfer, TEPA equivalent to 60ppm of the total amount of polyester in terms of phosphorus was added. After stirring for 15 minutes, TBT equivalent to 20ppm of the total amount of polyester in terms of titanium was added. Then, the polycondensation reaction was started by reducing the pressure and increasing the temperature from 225°C to 285°C and reducing the pressure to 25Pa. The final temperature and final pressure were reached in 90 minutes, and after a period of time, the melt viscosity of the reaction polymer system reached 2000poise and was discharged. When discharged, the polymer was in a uniform strip shape, and after cooling in a water tank, it was pelletized to obtain polyester composition slices. The specific formula and physical properties are shown in Table 4.
[0093] Since the dicarboxylic acid in the polyester composition is only an aromatic dicarboxylic acid, the refractive index of the obtained polyester composition is not significantly reduced and is higher than the target refractive index.
[0094] Comparative Example 3
[0095] 48.5 parts by weight of DMT, 16.7 parts by weight of CHDC, 48 parts by weight of CHDM, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring. Then, the ester exchange reaction was started. Under the set heating program, the temperature in the esterification reactor reached 220°C, and the by-product methanol was distilled out to obtain a small molecule polymer.
[0096] The obtained small molecule polymer was transferred to a polymerization kettle at a waiting temperature of 225°C. 5 minutes after the transfer, TEPA equivalent to 60ppm of the total amount of polyester in terms of phosphorus was added. After stirring for 15 minutes, TBT equivalent to 20ppm of the total amount of polyester in terms of titanium was added. Then, the polycondensation reaction was started by reducing the pressure and increasing the temperature from 225°C to 285°C and reducing the pressure to 25Pa. The final temperature and final pressure were reached in 90 minutes. After a period of reaction, the polymerization reaction was not completed, the reaction was terminated, and no polyester composition was obtained. The specific formula and physical properties are shown in Table 4.
[0097] Since the diols used as the polyester raw material did not contain a straight-chain aliphatic diol, the polymerization activity was poor and the target polyester composition was not obtained.
[0098] Comparative Example 4
[0099] 48.5 parts by weight of DMT, 16.7 parts by weight of CHDC, 41.3 parts by weight of EG, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring, and then the ester exchange reaction was started. The temperature in the esterification reactor reached 220°C under the set temperature increase program, and the by-product methanol was distilled out. When the distilled methanol reached the specified amount, the temperature in the esterification reactor was continued to be increased. After 30 minutes, the temperature in the reactor reached 230°C, and the excess EG in the esterification reactor was distilled out to obtain a small molecule polymer.
[0100] The obtained small molecule polymer is transferred to a polymerization kettle with a waiting temperature of 225°C. Five minutes after the transfer, TEPA equivalent to 60ppm of the total amount of polyester in terms of phosphorus is added. After stirring for 15 minutes, TBT equivalent to 20ppm of the total amount of polyester in terms of titanium is added. Next, the polycondensation reaction is started by reducing pressure and increasing temperature. The temperature is increased from 225°C to 285°C and the pressure is reduced to 25Pa. The final temperature and final pressure are reached in 90 minutes. After a period of time, the melt viscosity of the reaction polymer system reaches 2000poise and is discharged. The polymerization time from the beginning of reducing pressure and increasing temperature to the final discharge is 3 hours. When discharged, the polymer is in a uniform strip shape. After cooling in a water tank, it is pelletized to obtain polyester composition slices. The specific formula and physical properties are shown in Table 4.
[0101] Since the diols used as the polyester raw materials do not contain alicyclic diols with large steric hindrance, the gel of the obtained polymer is poor.
[0102] Comparative Example 5
[0103] 48.5 parts by weight of DMT, 16.7 parts by weight of CHDC, 35.1 parts by weight of EG, 14.4 parts by weight of CHDM, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring, and then the ester exchange reaction was started. The temperature in the esterification reactor reached 220°C under the set temperature increase program, and the by-product methanol was distilled out. When the distilled methanol reached the specified amount, the temperature in the esterification reactor was continued to be increased. After 30 minutes, the temperature in the reactor reached 230°C, and the excess EG in the esterification reactor was distilled out to obtain a small molecule polymer.
[0104] The obtained small molecule polymer is transferred to a polymerization kettle with a waiting temperature of 225°C. Five minutes after the transfer, TEPA equivalent to 60ppm of the total amount of polyester in terms of phosphorus is added. After stirring for 15 minutes, TBT equivalent to 0.5ppm of the total amount of polyester in terms of titanium is added. Next, the polycondensation reaction is started by reducing pressure and increasing temperature. The temperature is increased from 225°C to 285°C and the pressure is reduced to 25Pa. The final temperature and final pressure are reached in 90 minutes. After a period of time, the melt viscosity of the reaction polymer system reaches 2000poise and is discharged. The polymerization time from the beginning of reducing pressure and increasing temperature to the final discharge is 7 hours. When discharged, the polymer is in a uniform strip shape. After cooling in a water tank, it is pelletized to obtain polyester composition slices. The specific formula and physical properties are shown in Table 4.
[0105] Since the amount of titanium-based catalyst added to the polyester raw material is relatively small, the polymerization reaction time is very long, and the physical properties such as color tone of the obtained polyester composition are not good.
[0106] Comparative Example 6
[0107] 48.5 parts by weight of DMT, 16.7 parts by weight of CHDC, 35.1 parts by weight of EG, 14.4 parts by weight of CHDM, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring, and then the ester exchange reaction was started. The temperature in the esterification reactor reached 220°C under the set temperature increase program, and the by-product methanol was distilled out. When the distilled methanol reached the specified amount, the temperature in the esterification reactor was continued to be increased. After 30 minutes, the temperature in the reactor reached 230°C, and the excess EG in the esterification reactor was distilled out to obtain a small molecule polymer.
[0108] The obtained small molecule polymer is transferred to a polymerization kettle with a waiting temperature of 225°C. Five minutes after the transfer, TEPA equivalent to 60ppm of the total amount of polyester in terms of phosphorus is added. After stirring for 15 minutes, TBT equivalent to 110ppm of the total amount of polyester in terms of titanium is added. Next, the polycondensation reaction is started by reducing pressure and increasing temperature. The temperature is increased from 225°C to 285°C and the pressure is reduced to 25Pa. The final temperature and final pressure are reached in 90 minutes. After a period of time, the melt viscosity of the reaction polymer system reaches 2000poise and is discharged. The polymerization time from the beginning of reducing pressure and increasing temperature to the final discharge is 2 hours and 20 minutes. When discharged, the polymer is in a uniform strip shape. After cooling in a water tank, it is pelletized to obtain polyester composition slices. The specific formula and physical properties are shown in Table 4.
[0109] Since an excessive amount of the titanium-based catalyst is added to the polyester raw material, the obtained polyester composition has a high gel fraction and poor heat resistance.
[0110] Comparative Example 7
[0111] 48.5 parts by weight of DMT, 16.7 parts by weight of CHDC, 35.1 parts by weight of EG, 14.4 parts by weight of CHDM, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring, and then the ester exchange reaction was started. The temperature in the esterification reactor reached 220°C under the set temperature increase program, and the by-product methanol was distilled out. When the distilled methanol reached the specified amount, the temperature in the esterification reactor was continued to be increased. After 30 minutes, the temperature in the reactor reached 230°C, and the excess EG in the esterification reactor was distilled out to obtain a small molecule polymer.
[0112] The obtained small molecule polymer is transferred to a polymerization kettle with a waiting temperature of 225°C. Five minutes after the transfer, TEPA equivalent to 60ppm of the total amount of polyester in terms of phosphorus is added. After stirring for 15 minutes, TBT equivalent to 2ppm of the total amount of polyester in terms of titanium is added. Next, the polycondensation reaction is started by reducing pressure and increasing temperature. The temperature is increased from 225°C to 285°C and the pressure is reduced to 25Pa. The final temperature and final pressure are reached in 90 minutes. After a period of time, the melt viscosity of the reaction polymer system reaches 2000poise and is discharged. The polymerization time from the beginning of reducing pressure and increasing temperature to the final discharge is 6 hours. When discharged, the polymer is in a uniform strip shape. After cooling in a water tank, it is pelletized to obtain polyester composition slices. The specific formula and physical properties are shown in Table 4.
[0113] Although the amount of the titanium-based catalyst added is within an appropriate range, since the molar ratio of titanium element to phosphorus element is less than 0.05, the polymerization reaction time is long and the physical properties of the obtained polyester composition, such as color tone, are poor.
[0114] Comparative Example 8
[0115] 48.5 parts by weight of DMT, 16.7 parts by weight of CHDC, 35.1 parts by weight of EG, 14.4 parts by weight of CHDM, 0.06 parts by weight of MNA and 0.005 parts by weight of KOH were added to an esterification reactor, and the mixture was dissolved at 150°C while stirring, and then the ester exchange reaction was started. The temperature in the esterification reactor reached 220°C under the set temperature increase program, and the by-product methanol was distilled out. When the distilled methanol reached the specified amount, the temperature in the esterification reactor was continued to be increased. After 30 minutes, the temperature in the reactor reached 230°C, and the excess EG in the esterification reactor was distilled out to obtain a small molecule polymer.
[0116] The obtained small molecule polymer was transferred to a polymerization kettle with a waiting temperature of 225°C. Five minutes after the transfer, TEPA equivalent to 20ppm of the total amount of polyester in terms of phosphorus was added. After stirring for 15 minutes, TBT equivalent to 5ppm of the total amount of polyester in terms of titanium was added. Then, the polycondensation reaction was started by reducing pressure and increasing temperature. The temperature was increased from 225°C to 285°C and the pressure was reduced to 25Pa. The final temperature and final pressure were reached in 90 minutes. After a period of time, the melt viscosity of the reaction polymer system reached 2000poi se and was discharged. The polymerization time from the beginning of reducing pressure and increasing temperature to the final discharge was 2 hours and 15 minutes. When discharged, the polymer was in a uniform strip shape. After cooling in a water tank, it was pelletized to obtain polyester composition slices. The specific formula and physical properties are shown in Table 4.
[0117] Although the addition amount of the titanium-based catalyst is within an appropriate range, since the molar ratio of titanium element to phosphorus element is greater than 2.00, the obtained polyester composition has a high gel fraction and poor heat resistance.
[0118]
[0119]
[0120]
[0121]
Claims
1. A low refractive index polyester composition, characterized in that: The polyester composition mainly contains aromatic dicarboxylic acid units, alicyclic dicarboxylic acid units, diol units as shown in Formula 1, and diol units as shown in Formula 2 and / or Formula 3; the polyester composition contains titanium and phosphorus, the content of the titanium is equivalent to 1-100 ppm of the total amount of the polyester composition, and the molar ratio of the titanium to the phosphorus is 0.05-2.00; In formula 1, R 1 It is a chain alkylene group having 2 to 10 carbon atoms; In formula 2 and formula 3, R 2 is a cyclic alkylene group having 3 to 10 carbon atoms, R 3 ~R 6 are alkylene groups having 0 to 10 carbon atoms, R 7 ~R 8 Each of them is an alkyl group having 1 to 10 carbon atoms.
2. The low refractive index polyester composition according to claim 1, characterized in that: The alicyclic dibasic acid unit accounts for 10 to 50 mol% of the total dibasic acid unit content.
3. The low refractive index polyester composition according to claim 1 or 2, characterized in that: The sum of the diol units shown in Formula 2 and Formula 3 accounts for 5 to 90 mol% of the total diol unit content.
4. The low refractive index polyester composition according to claim 1, characterized in that: The polyester composition has a refractive index of 1.500 to 1.570 and a glass transition temperature of 50 to 100° C.
5. The low refractive index polyester composition according to claim 1, characterized in that: The polyester composition has a gel fraction of less than 10.0 wt % after heat treatment at 280° C.×24 hr in a nitrogen atmosphere.
6. The low refractive index polyester composition according to claim 1, characterized in that: The Haze content of the polyester composition is less than 5%.
7. The method for preparing the low-refractive index polyester composition according to claim 1, wherein dicarboxylic acid or its esterified derivative and diol are used as main monomers, and are added into an esterification kettle for esterification or transesterification reaction to obtain a small molecule polymer, and then the small molecule polymer is subjected to polycondensation reaction to obtain the low-refractive index polyester composition; wherein: The dicarboxylic acid or its esterified derivative includes aromatic dicarboxylic acid or its esterified derivative and alicyclic dicarboxylic acid or its esterified derivative; the diol includes the diol shown in Formula 4 and the diol shown in Formula 5 and / or Formula 6; a titanium catalyst and a phosphorus compound are added during the polymerization process, the titanium catalyst is added in an amount of 1 to 100 ppm relative to the total amount of the polyester composition in terms of titanium element, and the titanium catalyst and the phosphorus compound are added in an amount of 0.05 to 2.00 in a molar ratio of titanium element to phosphorus element; HO-R1-OH formula 4, In formula 4, R 1 It is a chain alkylene group having 2 to 10 carbon atoms; In equations 5 and 6, R 2 is a cyclic alkylene group having 3 to 10 carbon atoms, R 3 ~R 6 are alkylene groups having 0 to 10 carbon atoms, R 7 ~R 8 Each of them is an alkyl group having 1 to 10 carbon atoms.
8. The method for preparing the low refractive index polyester composition according to claim 7, characterized in that: The titanium catalyst is tetraethoxytitanium, tetrapropoxytitanium, tetraisopropoxytitanium, tetra-n-butoxytitanium, tetrahexyloxytitanium, tetra-2-ethylhexyloxytitanium, tetraoctyloxytitanium, monohydroxytriethoxytitanium, monohydroxytripropoxytitanium, monohydroxytriisopropoxytitanium, monohydroxytributoxytitanium, dihydroxybisethoxytitanium or trihydroxyisopropoxytitanium.
9. The method for preparing the low refractive index polyester composition according to claim 7 or 8, characterized in that: The phosphorus compound is phosphoric acid, sodium dihydrogen phosphate, triethyl phosphoacetate, trimethyl phosphoacetate or triphenyl phosphate.
10. Use of the low refractive index polyester composition according to claim 1 in polyester film.
Citation Information
Patent Citations
Polyester resin
JP2003020330A